Predicting Price and Risk ICBP Stocks Using GRU and VaR - Ryan Dana, Alvin; Trimono, Trimono; Idhom, Mohammad (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2025)
The economy plays a vital role in maintaining a country’s stability and progress, where stock investments serve as a primary financial instrument to enhance societal welfare. In Indonesia, interest in stock investments, especially in the essential food sector, continues to grow due to its long-term profit potential. This study combines stock price prediction with risk analysis using a Gated Recurrent Unit (GRU) model and Value at Risk (VaR) calculation based on historical simulation. The GRU model is selected for stock price prediction due to its ability to capture complex, fluctuating patterns and adapt to market changes, while VaR is used to measure potential maximum loss at a 95% confidence level. The findings indicate a potential loss of IDR 65.785, demonstrating that this approach can provide a risk estimate by combining future predicted prices with historical data. Thus, this approach offers guidance for investors in understanding potential profits and risks in stock assets. The integration of GRU-based predictions and historical simulation VaR is expected to support more informative and prudent investment decision-making, particularly in facing the dynamic and risky stock market conditions.